2021
DOI: 10.1002/ange.202106531
|View full text |Cite
|
Sign up to set email alerts
|

Selective C–F Bond Allylation of Trifluoromethylalkenes

Abstract: Selective CÀF bond functionalization of CF 3 group represents an appealing strategy for the incorporation of pharmaceutically privileged difluoromethylene moiety. Despite the recent significant advancement attained in the functionalization of Ar-CF 3 molecules, prescriptions amenable for alkenyl-CF 3 congeners remain sufficiently inadequate. Herein, we report a strategically novel protocol for the CÀF bond elaboration of trifluoromethylalkene derivatives. By using readily available allyl metallics as nucleophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…[23] In addition, the defluorination of 4 aa with LiAlH 4 was observed in excellent stereoselectivity (> 20 : 1 E/Z), giving 68 % yield of mono-fluoro substituted alkene 15. [24] The stereo configuration of product 15 was determined by NOE spectra (see Supporting Information for details). Notably, by choosing proper catalyst, the chemoselective hydrogenation was also a touchable task.…”
Section: Methodsmentioning
confidence: 99%
“…[23] In addition, the defluorination of 4 aa with LiAlH 4 was observed in excellent stereoselectivity (> 20 : 1 E/Z), giving 68 % yield of mono-fluoro substituted alkene 15. [24] The stereo configuration of product 15 was determined by NOE spectra (see Supporting Information for details). Notably, by choosing proper catalyst, the chemoselective hydrogenation was also a touchable task.…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] Our group has long been interested in the selective C—F bond activation. [ 13 ] In 2017, we reported a rhodium‐catalyzed [4 + 1] annulation reaction with gem ‐difluoromethylene alkynes, which are readily prepared from terminal alkynes, as an uncommon C1 unit for the construction of isoindolin‐1‐one derivatives. Mechanistic study suggested successive dual C—F bond cleavage as the crucial steps for the transformation.…”
Section: Background and Originality Contentmentioning
confidence: 99%